Detecting and Tuning the Interactions between Surfactants and Carbon Nanotubes for Their High‐Efficiency Structure Separation. Issue 2 (1st December 2017) - Zeng, Xiang; Yang, Dehua; Liu, Huaping; Zhou, Naigen; Wang, Yanchun; Zhou, Weiya; Xie, Sishen; Kataura, Hiromichi
Abstract: The selective interaction is systematically explored between the surfactants (sodium deoxycholate (DOC), sodium dodecyl sulfate (SDS), and sodium cholate (SC)) and the single‐wall carbon nanotubes (SWCNTs) by the gel chromatography technique. The results show that DOC preferentially interacts with small‐diameter semiconducting SWCNTs (S‐SWCNTs), exhibiting the strongest interaction strength for the SWCNTs, and the highest structural selectivity. The surfactant SC shows high selectivity toward the chiral angles of the SWCNTs. Its interaction strength and structural recognition ability are slightly higher than that of SDS but lower than that of DOC. Combining with the proved selectivity of SDS in the adsorption onto the S‐SWCNTs with small CC bond curvature, it is discovered that the synergistic effect of the triple surfactants amplified the interaction difference among the different SWCNTs and the gel, and thus dramatically improved the separation efficiency and structural purity of the SWCNTs, achieving the separation of distinct ( n, m ) single‐chirality species and their enantiomers in one step. This work not only provides deeper insights into the separation mechanism of SWCNTs with the surfactant sorting techniques, but also has a profound significance in studying the interaction between the SWCNTs and other small molecules. Abstract : One‐pot separation of single‐chirality carbon nanotubes and their enantiomers is achieved by a cosurfactant system, in which the different selectivity of sodium cholate, sodium deoxycholate, and sodium dodecyl sulfate toward the chiral angles, diameters, and C‐C bond curvatures of the nanotubes is used to synergistically enhance the structural recognition of the distinct ( n, m ) species.